INTER-ORGANELLAR CA2+ SIGNALING IN HEALTH AND DISEASE (International Review of Cell and Molecular Biology, 2021)
International Review of Cell and Molecular Biology reviews and details current advances in cell and molecular biology. The IRCMB series has a worldwide readership, maintaining a high standard by publishing invited articles on important and timely topics that are authored by prominent cell and molecular biologists. The articles published in IRCMB have a high impact and an average cited half-life of 9 years. This great resource ranks high amongst scientific journals dealing with cell biology.